PENINGKATAN HASIL BELAJAR IPS DENGAN TIPE NUMBERED HEAD TOGETHER DI SDN 24 PONTIANAK TENGGARA - Mariani, Hajar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aimed to describe the learning outcome of students in learning social studies in grade VB SD Negeri 24 Southeast Pontianak by implementing cooperative learning model Numbered Head Together (NHT). The method used in this research is descriptive. Form of research is classroom action research. The nature of research is collaborative. The subjects of this study were teacher as a researcher and 21 students of class VB SDN 24 Southeast Pontianak, which  7 male students and 14 female students. Research procedure includes four stages: Planning, Implementing, Observations and Reflections. This study was conducted by two cycles. The results of the research are: 1) The ability of teacher’s planning Social Sciences learning has increased from cycle I to cycle II about 17.65%. 2) The ability of teachers in implementing the learning of Social Sciences has increased from cycle I to cycle II about 8%. 3) The average of students learning outcomes has increased from the first cycle to the second cycle about 31.67 to be 92.62. Keywords: Numbered Head Together,  Learning Outcomes, Social Science